Malabaricone C from Myristica Cinnamomea exhibits Anti-Quorum sensing activity - Chong, Y.M.; Yin, W.F.; Ho, C.Y.; Mustafa, Mohd Rais; Hadi, A.H.A.; Awang, K.; Narrima, P.; Koh, C.L. (2011)
A methanol-soluble extract of the bark of Myristica cinnamomea was found to exhibit anti-quorum sensing activity, and subsequent bioassay-guided isolation led to the identiﬁcation of the active compound malabaricone C (1). Compound 1 inhibited violacein production by Chromobacterium violaceum CV026 when grown in the presence of a cognate signaling molecule, N-3-oxohexanoyl-homoserine lactone. Furthermore, 1 inhibited the quorum sensing-regulated pyocyanin production and bioﬁlm formation in Pseudomonas aeruginosa PAO1. These results suggest that the anti-quorum sensing activity of 1 and related molecules should be investigated further